A Study Based on the Knowledge, Attitudes, and Practices Regarding COVID-19, Vaccines and Non-pharmaceutical Interventions (NPIs): An International Survey - Momo Djonjue, Laure Carole (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background The COVID-19 outbreak posed a significant global threat, necessitating the swift deployment of stringent measures to mitigate its spread and impact. Central to effectively managing such crises thorough assessments of population health must be performed and should be underpinned by the recognition that knowledge acquisition plays a pivotal role in shaping behavioral responses. In this context, the Knowledge, Attitudes, and Practices (KAP) model emerges as a robust diagnostic framework. This study aims to assess residents' understanding, attitudes, and behaviors regarding the 2019 coronavirus, vaccines, and non-pharmaceutical interventions in Cameroon and Canada. Using the KAP model, we seek to explore how knowledge, attitudes, and practices interact, providing insights for future targeted interventions and disease control measures. Methods An anonymous online survey was randomly administered amongst 166 participants in Cameroon and Canada via SurveyMonkey between October 25, 2022, and February 25, 2023. Descriptive and stratified analyses quantified residents’ responses to KAP. The data was analyzed through both qualitative and quantitative approaches. The analytical protocol included descriptive data analyses followed by an assessment of independent factors associated with KAP. Correlations were assessed between the dependent variables. A linear regression was employed to identify predictors related to KAP scores. A scoping review was conducted to map existing evidence on COVID-19, KAP, vaccines, and NPIs using Cochrane guidelines, including 35 international studies published between December 2019 and September 2022. The review aimed to examine factors influencing COVID-19 vaccine acceptance, intention, and hesitancy, and to develop a conceptual framework for these factors and NPIs globally. Covidence was used for screening articles following inclusion and exclusion criteria. Results 73.5% of participants identified as youths within 18-25 years of age. Data analysis revealed that there was a significant correlation between knowledge and practices (r = 0.249, p<.001). Further, residence, marital status, and educational level were identified as significant predictors of KAP. These findings also demonstrated that Canadians displayed higher knowledge levels and adherence to recommended guidelines, whereas Cameroonians exhibited better attitudes, yet less adherence to COVID-19 protocols, non-pharmaceutical interventions (NPIs), and vaccination. Conclusion Conclusively, our observations revealed that the level of public knowledge was significantly correlated to the level of practices. The higher the level of knowledge of the participants, the better the practices. In addition, the level of education and marital status were identified as strong predictors of KAP. These data underscore that importance of knowledge dissemination for the spread of communicable diseases related to COVID outbreaks, as it will help with adherence to disease prevention strategies. Abstrait Introduction L’épidémie de la COVID-19 a constitué une menace mondiale importante, suivie de la mise en œuvre de mesures rigoureuses adoptées par l’urgence nationale pour contrôler sa propagation massive. L’évaluation de la santé d’une population est primordiale pour faciliter l’éradication des maladies, l’acquisition de connaissances est un facteur primordial dans le changement de comportement, et le modèle CAP a été identifié comme un outil de diagnostic puissant. Cette étude vise à évaluer la compréhension, les attitudes et les comportements des résidents concernant le coronavirus 2019, les vaccins et les interventions non-pharmaceutiques au Cameroun et au Canada. À l’aide du modèle CAP, nous cherchons à explorer comment les connaissances, les attitudes et les pratiques interagissent, en fournissant des informations pour des interventions ciblées et des mesures de contrôle des maladies. Une revue de la portée a été effectuée pour améliorer la robustesse de la thèse en cartographiant systématiquement les preuves existantes sur le terrain. Méthode Un sondage anonyme en ligne a été administré au hasard à 166 participants au Cameroun et au Canada via Survey Monkey entre le 25 octobre 2022 et le 25 février 2023. Des analyses descriptives et stratifiées ont permis de quantifier les réponses des résidents au CAP. Les données ont été analysées à l’aide d’approches qualitatives et quantitatives à l’aide de Survey Monkey et de SPSS. Le protocole d’analyse comprenait des analyses de données descriptives. Une corrélation a été évaluée entre les variables dépendantes et indépendantes. Un modèle de régression linéaire a été utilisé pour identifier les prédicteurs liés aux scores CAP. Une revue a été menée pour cartographier les données probantes existantes sur la COVID-19, les CAP, les vaccins et les INPs à l’aide des lignes directrices Cochrane. L’examen visait à examiner les facteurs influençant l’acceptation, l’intention et l’hésitation du vaccin contre la COVID-19, et à élaborer un cadre conceptuel pour ces facteurs et les INPs à l’échelle mondiale. Covidence a été utilisé pour filtrer les articles selon des critères d’inclusion et d’exclusion et 35 études internationales ont été identifier Résultats 73.5% des participants s’identifiaient comme des jeunes-adultes. Le test statistique réalisé a révélé qu’il existait une corrélation significative entre les connaissances et les pratiques (r=0,249, p<,001). Le lieu de résidence, l’état matrimonial et le niveau de scolarité ont été identifiés comme de bons prédicteurs de la CAP à la signification à p<. 001. Les résultats ont montré que les Canadiens affichaient des niveaux de connaissances et de respect des lignes directrices recommandées plus élevés, tandis que les Camerounais affichaient de meilleures attitudes, mais des niveaux inférieurs de connaissances et d’adhésion aux protocoles COVID-19, aux interventions non pharmaceutiques (INPs) et à la vaccination. Conclusion En conclusion, le niveau de connaissance était significativement corrélé au niveau des pratiques. Plus le niveau de connaissance des participants est élevé, plus le niveau de pratiques est élevé. De plus, le niveau d’éducation et l’état matrimonial ont été identifiés comme de puissants prédicteurs de la CAP. Il est nécessaire de comprendre la propagation des maladies transmissibles d’un pays à l’autre, car cela facilitera la prise de décision et la mise en œuvre de stratégies de prévention des maladies.
Keywords: Knowledge; Attitudes; Practices; Behavio*; COVID-19; Vaccines; Non-pharmaceutical Interventions (NPIs)